2014
DOI: 10.1001/jamapsychiatry.2013.2842
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Recall of Life Events in Conversion Disorder

Abstract: IMPORTANCE Freud argued that in conversion disorder (CD) the affect attached to stressful memories is "repressed" and "converted" into physical symptoms, although this has never been subject to scientific study to our knowledge. OBJECTIVE To examine the neural correlates of recall of life events judged to be of causal significance in CD. DESIGN, SETTING, AND PARTICIPANTS Case-control study. Academic research setting among 12 patients with motor CD and 13 healthy control subjects. MAIN OUTCOMES AND MEASURES Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
131
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 53 publications
(48 reference statements)
14
131
0
2
Order By: Relevance
“…As mentioned in the introduction we have recently reported enhanced connectivity between the amygdala and the SMA in an emotional memory task providing a link between areas involved in emotional and motor control. [4] A similar limbic-motor interaction has been shown during an implicit emotion task similar to the present study with increased amygdala and SMA functional connectivity along with some evidence of a failure to habituate to the emotional stimulus [5]. Interestingly, a failure to habituate to aversive stimuli has been long recognised as a feature of 'hysteria' since the late 19 th century and has been replicated in behavioral studies [22].…”
Section: Discussionsupporting
confidence: 85%
“…As mentioned in the introduction we have recently reported enhanced connectivity between the amygdala and the SMA in an emotional memory task providing a link between areas involved in emotional and motor control. [4] A similar limbic-motor interaction has been shown during an implicit emotion task similar to the present study with increased amygdala and SMA functional connectivity along with some evidence of a failure to habituate to the emotional stimulus [5]. Interestingly, a failure to habituate to aversive stimuli has been long recognised as a feature of 'hysteria' since the late 19 th century and has been replicated in behavioral studies [22].…”
Section: Discussionsupporting
confidence: 85%
“…Aybek and colleagues (2015) reported enhanced amygdala responses to threat signals (fearful faces) in FND patients, suggesting impaired emotional regulation, while Voon et al (2010a) demonstrated increased functional connectivity between the amygdala and SMA when viewing fearful and happy faces in patients with "productive" functional motor symptoms (e.g., tremor, dystonia). Enhanced amygdala-SMA connectivity, together with increased dorsolateral prefrontal cortex and decreased hippocampus activity, was also reported during recall of autobiographical traumatic events in functional paresis (Aybek, et al, 2014). These results may be due to higher states of emotional arousal associated with FND (Horvath, et al, 1980;Lader and Sartorius, 1968).…”
Section: Introductionmentioning
confidence: 88%
“…For instance, greater amygdala activity has been observed with arousing stimuli in motor FND with enhanced amygdala-SMC FC observed with arousing 162 and negative events. 167 Similarly, in functional mutism, greater FC was observed between the IFC and amygdala. 163 The SMC is implicated in processes of motor initiation, intention, and urge and also in inhibitory processes.…”
Section: Summary Of Implicated Neural Regionsmentioning
confidence: 96%
“…160 In a single case study in functional paralysis, Kanaan et al 166 showed greater amygdala and right inferior frontal activity and decreased motor activity to cued recall of a clinically repressed emotional event compared with other severe personal events. In an extension of this study, Aybek et al 167 compared stressful life events assessed using the Life Events Difficulties Schedule among patients with motor FND (N=12) compared with healthy controls (N=13), focusing on escape (based on the threat and extent to which illness might allow escape from the consequences) compared with severity (equally threatening control events). The escape events were associated with longer reaction times and were perceived as less upsetting than severe events.…”
Section: Arousal and Traumamentioning
confidence: 99%